PENGARUH TIPE INDUSTRI DAN KEPEMILIKAN INSTITUSIONAL TERHADAP INTERNET FINANCIAL REPORTING - Muhammad Riduan Abdillah; Indra Saputra (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2025)
The purpose of this research is to empirically examine the effect of industry type and institutional ownership on Internet Financial Reporting. Population of this research is all companies listed on the Indonesia Stock Exchange in 2024. This research sampling technique uses purposive sampling method. This research uses quantitative research methods. The independent variables of this research are industry type and institutional ownership. The dependent variable of this research is Internet Financial Reporting (IFR). This research uses secondary data through the company's web, the Indonesia Stock Exchange web and the Company's Annual Report. This research data analysis uses multiple linear regression analysis. The results of that industry type has a significant effect on Internet Financial Reporting (IFR) and institutional ownership has an effect on Internet Financial Reporting.